Composition and technology development of ear drops with cerumenolytic action (based on thick Viscum album L. leaves extract) - A. E. Pozdnyakova; S. L. Adzhiakhmetova; E. O. Sergeeva; D. I. Pozdnyakov; E. A. Yurtaeva; I. O. Borodina; D. V. Kompantsev (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2024)
Earwaxes lead to a decrease in the quality of life. A rational and effective way to eliminate earwaxes without a participation of medical personnel is to use ear drops and solutions to dissolve sulfur masses. In this regard, therapeutic and hygienic drops of а cerumenolytic action are of a particular relevance in the pharmaceutical market.The aim of the work was to develop a composition and technology of ear drops of a cerumenolytic action based on thick Viscum Album L. leaves extract.Materials and methods. The objects of the study were thick Viscum Album L. leaf extract, chitosan, sodium alginate, polyethylene oxide of various degrees of polymerization, propylene glycol, sodium hyaluronate, preservatives (benzalkonium chloride, nipagine and nipazole). At the screening stage, 9 experimental formulations were proposed. The cerumenolytic activity of the developed formulations was evaluated in a dissolution test of reproduced artificial earwax in comparison with a 3% hydrogen peroxide solution, TEA-cocoyl hydrolyzed collagen (A-Cerumen Plus, Gilbert Laboratories, France) and a 0.9% sodium chloride solution. Physical and chemical parameters (a degree of liquid coloring, turbidity and transparency, pH, density and viscosity) were determined according to of the State Pharmacopoeia of the Russian Federation (XV ed.). The microbiological study was performed using the agar diffusion method.Results. In the course of the study, it was shown that the composition of ear drops of a cerumenolytic action based on thick Viscum Album L. leaves extract, exceeds the level of a lipolytic, proteolytic and general cerumenolytic kinds of activity of the compositions containing surfactants; in its effectiveness, it was comparable with the comparison drug - A-Cerumen drops. To obtain the optimal rate of the onset effect and its duration, it is advisable to use sodium hyaluronate in the amount of 0.2 g per 25 ml of drops as an adjuvant. The most preferred preservative was benzalkonium chloride. The developed ear drops met the requirements of the State Pharmacopoeia of the Russian Federation (XV ed.) for this dosage form, while the pH was 5.86± 0.1, and the viscosity was 4.2676±0.2 MPa×s.Conclusion. The conducted research has shown the prospects for further work on the development and implementation of ear drops of a cerumenolytic action in practice. The recommended composition is the following: thick Viscum Album L. leaf extract, sodium hyaluronate, benzalkonium chloride, purified water.